Induced pluripotent stem cells representing Nakajo-Nishimura syndrome - Nobuo Kanazawa; Fumiko Honda-Ozaki; Megumu K. Saito (BMC, 2019)
Abstract Nakajo-Nishimura syndrome is a proteasome-associated autoinflammatory syndrome with a distinct homozygous mutation in the PSMB8 gene encoding an inducible β5i subunit of the immunoproteasome. Although it is considered that immunoproteasome dysfunction causes cellular stress and contributes to the production of inflammatory cytokines and chemokines, its detailed mechanism is still unknown. On the other hand, hereditary autoinflammatory diseases are considered as a good target for the analyses using induced pluripotent stem cells, whose differentiation systems to the innate immune cells such as neutrophils and monocytes have been established. Therefore, to elucidate the pathogenesis of Nakajo-Nishimura syndrome, we attempted in vitro disease modeling using patient-derived induced pluripotent stem cells. For analyses, isogenic control cells in which the responsible mutation was repaired and another pair of healthy embryonic stem cells and isogenic mutant cells in which the same mutation was introduced had also been prepared with genetic engineering. By comparing a pair of isogenic cells with the wild-type and the mutant PSMB8 gene after differentiation into monocytes and immortalization to synchronize their differentiation stages, the reduction of immunoproteasome enzyme activity and increased cytokine and chemokine production in the mutant cells without stimulation or with interferon-γ plus tumor necrosis factor-α stimulation were observed, and therefore, the autoinflammatory phenotype was successfully reproduced. Decreased cytokine production was observed by the addition of antioxidants as well as inhibitors for Janus kinase and p38-mitogen-activated protein kinase. At the same time, the increased production of reactive oxygen species and phosphorylation of both signal transducers and activator of transcription 1 and p38-mitogen-activated protein kinase were detected without stimulation. Notably, an antioxidant specifically decreased the constitutive phosphorylation of signal transducers and activator of transcription 1. These results indicate the usefulness of a disease modeling using pluripotent stem cell-derived cells in clarification of the pathomechanism and discovery of new therapeutic drugs for Nakajo-Nishimura syndrome and related proteasome-associated autoinflammatory syndromes.